2005
DOI: 10.1515/hf.2005.103
|View full text |Cite
|
Sign up to set email alerts
|

Contact-free measurement and non-linear finite element analyses of strain distribution along wood adhesive bonds

Abstract: The strain distribution along wood adhesive bonds was studied using a contact-free measurement system based on a white-light digital image correlation (DIC) technique. Two different specimen geometries and three different adhesives were investigated. The specimen geometries were according to the standards EN302-1 and ASTM D905. The adhesives tested were a phenolic resorcinol (PRF), a one-component polyurethane (PUR) and an epoxy (EPX). In addition to the experimental investigation, a finite element study using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 5 publications
3
27
0
Order By: Relevance
“…The use of DIC techniques in connection with wood or wood-based products is, however, rather limited. A review of research carried out up to the year 2005 is found in Serrano and Enquist (2005) where results from an investigation into strain distribution along wood adhesive bonds using DIC technique are presented. In recent years, the technique has been used for the measurements of, for example, strain in steel-to-timber dowel joints (Sjödin et al 2006), strain in bi-axially loaded sheathing-to-framing connections (Vessby et al 2008), strain distribution in timber subjected to four-point bending tests (Murata et al 2005), strain-softening behaviour of wood under tension perpendicular to the grain (Miyauchi and Murata 2007) and tensile properties of early wood and late wood of loblolly pine (Young Jeong et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The use of DIC techniques in connection with wood or wood-based products is, however, rather limited. A review of research carried out up to the year 2005 is found in Serrano and Enquist (2005) where results from an investigation into strain distribution along wood adhesive bonds using DIC technique are presented. In recent years, the technique has been used for the measurements of, for example, strain in steel-to-timber dowel joints (Sjödin et al 2006), strain in bi-axially loaded sheathing-to-framing connections (Vessby et al 2008), strain distribution in timber subjected to four-point bending tests (Murata et al 2005), strain-softening behaviour of wood under tension perpendicular to the grain (Miyauchi and Murata 2007) and tensile properties of early wood and late wood of loblolly pine (Young Jeong et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, such a sophisticated model needs much more experimental and computational effort. Moreover, a superior finite-element code with advanced material description options is required, as proposed by Serrano (1997) and Serrano and Enquist (2005). MARC, which is a standard non-linear finite element code with superior non-linear material features, is a good candidate for such simulations (Hardtke et al 1997;Scheffler 2001).…”
Section: Discussionmentioning
confidence: 99%
“…2. The principle of DIC and the detailed test procedures were described in previous papers (Serrano and Enquist 2005;Jeong et al 2009). The core of DIC is the monitoring of the in-plane displacements on a plane object by tracking the deformation of a random pattern in an image (Valla et al 2011).…”
Section: Shear Strain Measurement By Dicmentioning
confidence: 99%
“…In fact, mechanical characterization on a micro scale can give information about strain and stress concentration, which is of great significance to the materials. As one of the non-contact measurement techniques that characterizes strain distribution on material surfaces on a micro level, digital image correlation (DIC) has been used in wood materials for some time (Zink et al 1995;Serrano and Enquist 2005;Muszyński et al 2006;Jeong et al 2009). In the present study, we used DIC to measure the shear strain distribution on the wood/adhesive interphase of both treated and untreated lap joint specimens, thereby evaluating the effects of these treatments.…”
Section: Introductionmentioning
confidence: 99%